Fabrication of Soccer and Cricket Ball Launching Machine - I.Raghuram; G.Jaya Surya; P.Joseph; Ch.Vijaya Krishna Rao; B.Susmitha (International Journal of Engineering and Management Research, 2023)
There are so many famous games in the world. In that, soccer and cricket are the two famous games played by a team of members. Now a day’s school/college/university doesn’t have sufficient trainers to train the students in respective sports like soccer and cricket. Even though they have trainers they don't have sufficient time to train the individual students in specific field at a time. For this reason our paper focus on introducing a launching machine known as soccer & cricket ball launching machine to train the goal keeper by himself in ground without help of a trainer or any other person So by using this machine we can give training to their students in respective field of sports like soccer and cricket. This machine throws the balls automatically at different suitable adjustable speeds. Launching of the ball in horizontal and vertical planes and in trajectory motions using aerodynamic and mechanical principals. This machine is useful in both games and also machine works efficiently in their practice. While using this machine we can save the time for trainers because the balls are thrown automatically and also students who are using this machine do practice efficiently when compared to the trainer training the students. And also this single machine plays a major role for practicing in both soccer and cricket sports.